Pengaruh Transparansi, Akuntabilitas dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa: Studi pada Desa Purwosari Kecamatan Natar Kabupaten Lampung Selatan - Chrisma Angellicca Rivera; Siti Khoirina; Dewi Silvia (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The method used in this research is quantitative descriptive where the data processing is carried out statistically and then the data used is primary data in the form of a questionnaire. The population in this study were village officials and village communities in Purwosari, Natar District and the sampling technique used a saturated sampling method with a sample size of 35 respondents consisting of 18 village officials and 17 Purwosari village residents. data testing using SPSS version 25. The results of the analysis showed that Transparency has a significant effect on the management of village funds with the acquisition of a t count of 2,915 with a significance value of 0,007 less than 0,05. Accountability had no significance effect on village fund management with a t count of 0,675 with a significance value of 0,505 greater than 0,05. Community participation has a significant effect on management of village funds with the acquisition of a t count of 3,631 with a significance value of 0,001, less than 0,05.